13C-egg white breath test: a non-invasive test of pancreatic trypsin activity in the small intestine. Issue 1 (1st January 2000) - Evenepoel, P; Hiele, M; Geypens, B; Geboes, K P; Rutgeerts, P; Ghoos, Y
Abstract : BACKGROUND: The recent availability of egg white protein highly enriched with 13 C has allowed breath test technology to be adapted for the study of protein digestion and absorption. Pancreatic trypsin is considered to be the key enzyme in the proteolytic cascade. AIM: To evaluate trypsin activity in the small intestine of healthy volunteers and patients with pancreatic disease by a recently developed 13 C-egg white breath test. METHODS: A total of 48 healthy volunteers and 30 patients with pancreatic disease were studied after ingestion of a test meal consisting of 22 g 13 C-labelled egg protein. Breath samples were taken before and after ingestion of the meal and analysed for 13 CO2 concentration. Moreover, pancreatic trypsin output after maximal stimulation was measured in 13 patients and nine healthy volunteers. RESULTS: The six hour cumulative 13 CO2 excretion in breath was significantly lower in patients than controls (mean (SEM): 6.23 (0.82)% v 19.16 (0.58)%, p<0.0001). An excellent correlation was found between the six hour cumulative 13 CO2 excretion and trypsin activity after maximal pancreatic stimulation. CONCLUSION: The non-invasive 13 C-egg white breath test is promising as an indirect pancreatic proteolytic function test.